Empirical Development of an Exponential Probabilistic Model for Text Retrieval: Using Textual Analysis to Build a Better Model - Teevan, Jaime; Karger, David R. (Proceedings of the 26th Annual ACM Conference on Research and Development in Information Retrieval, Toronto, Canada, 2003)
Much work in information retrieval focuses on using a model of documents and queries to derive retrieval algorithms. Model based development is a useful alternative to heuristic development because in a model the assumptions are explicit and can be examined and refined independent of the particular retrieval algorithm. We explore the explicit assumptions underlying the nave Bayesian framework by performing computational analysis of actual corpora and queries to devise a generative document model that closely matches text. Our thesis is that a model so developed will be more accurate than existing models, and thus more useful in retrieval, as well as other applications. We test this by learning from a corpus the best document model. We fi nd the learned model better predicts the existence of text data and has improved performance on certain IR tasks.